The effect of green area management style in (some Iraqi stadiums) on some soil biological properties Using geospatial applications - J. Saleh, Zainab; Almashhadnai, Haleema (Journal of Physical Education, 2024)
A field study was carried out to study the variations in some of the biological characteristics of the green areas within two football fields (Al-Karkh stadiums in Baghdad Governorate and Najaf Stadium in Najaf Governorate). Due to the heterogeneity of the management methods used, so dirt samples were obtained from the depth of 0-30 cm after determining geographical locations 5 drill hole site examined at each stadium, and base maps were produced for the study areas using Google earth, with the aim of studying the impact of football stadium management style on some soil pedological characteristics. The results of the volumetric distribution of the soil separations of the surface samples of the playgrounds showed that the coarse texture is predominant in the two playgrounds, as the predominance in them is for the sand separated. The results also indicate a decrease in the bulk density values of all surface samples of the two playgrounds despite the predominance of the coarse separation in all surface samples, if Which was reflected in the values of porosity, as the results showed a disparity in the values of porosity in the stadiums. The results indicate a low salinity These results are consistent with the nature of the management method followed, and it was found that there is a variation in the values of organic carbon content, as the concentration of organic carbon in the soil is affected by soil management, and From the calculation of the readiness index of elements, it was found that the nitrogen readiness index was moderate in Karkh stadium, while Najaf stadium had a low nitrogen readiness index, while the phosphorus readiness index was high in Karkh and Najaf stadiums, while the potassium readiness index was low in Najaf stadium and medium in Karkh stadium.